Programming in C++ for engineering and science - Nyhoff, Larry R. (CRC Press, 2013)
"Developed from the author's many years of teaching computing courses, Programming in C++ for Engineering and Science guides readers in designing programs to solve real problems encountered in engineering and scientific applications, including radioactive decay, pollution indices, digital circuits, differential equations, Internet addresses, data analysis, simulation, quality control, electrical networks, data encryption, and beam deflection. To make it easier for novices to develop programs, the author uses an object-centered design approach that helps readers identify the objects in a problem and the operations needed; develop an algorithm for processing; implement the objects, operations, and algorithm in a program; and test, correct, and revise the program. He also revisits topics in greater detail as the text progresses. By the end of the book, readers will have a solid understanding of how C++ can be used to process complex objects, including how classes can be built to model objects. Features: Uses standard C++ throughout - Explains key concepts, such as functions and classes, through a "use it first, build it later" approach - Shows how to develop programs to solve real problems, emphasizing the proper techniques of design and style - Introduces the very powerful and useful Standard Template Library along with important class and function templates - Presents examples of developing numeric techniques and programs for engineering and science problems - Highlights key terms, important points, design and style suggestions, and common programming pitfalls in the chapter summaries - Includes self-study questions and programming projects in each chapter - Provides ancillary materials on the book's website"--Provided by publisher.